Data-Driven Computations in the Life Sciences - Pires, Marília (2015)
Mathematical modeling and simulations in the Life Sciences is a very ambitious and rapidly developing interdisciplinary research field that connects mathematics, computational sciences and engineering to biology and medicine. Starting from high-resolution volumetric medical imaging, the development of spatially realistic physiological models for predictive medicine leads to complex mathematical models to capture heterogeneous processes of multiscale nature, that require highly efficient numerical algorithms and high performance computing techniques for their simulation. The aim of he School is to bring together doctoral candidates, postdoctoral scientists and graduates in applied mathematics, bioengineering and medicine, who wish to be involved in this fascinating research field, giving them the opportunity to make scientific interactions and new connections with established experts in the different topics covered by these events.